Trichomonosis in Greenfinches (Chloris chloris) in the Netherlands 2009–2017: A Concealed Threat - Rijks, Jolianne M.; Laumen, Andrea A. G.; Slaterus, Roy; Stahl, Julia; Gröne, Andrea; Kik, Marja L. (Frontiers in Veterinary Science, 2019)
Finch trichomonosis in Europe is caused by a Trichomonas gallinae subtype A1 strain, considered to be clonal because lacking genetic heterogeneity in partial genotyping. The disease recently emerged and has been associated with a 66% reduction of the British breeding greenfinch (Chloris chloris) population. In contrast, in the Netherlands, where trichomonosis was detected in 2009, the breeding greenfinch population continued to grow in subsequent years. This study aimed to elucidate whether this discrepancy in population trends is because Trichomonas infection in Dutch greenfinches is associated with less severe disease, i.e., disease being less fatal. Therefore, it characterised and quantified trichomonosis in a convenience sample of greenfinches found dead and examined post-mortem between 2009 and 2017 and compared results to published data from Great Britain. Trichomonads were detected by cytology, histology, or culture in 95/101 greenfinches. The birds with trichomonads all had microscopic lesions in the upper digestive tract consistent with trichomonosis, indicating the trichomonads caused disease. The occurrence of significant lesions due to other causes was low. Some greenfinches with trichomonosis showed no macroscopic lesions. These birds showed significantly less ulceration of the mucosa and less extensive heterophil infiltration, but extent of macrophage infiltration and presence of bacteria was similar to that of birds with macroscopic lesions, and significant lesions due to other causes were equally rare. Therefore, trichomonosis was considered similarly fatal in both groups. The frequency of fatal trichomonosis in the Dutch greenfinches did not differ significantly from that reported from Great Britain. Partial genotyping of the ITS1-5,8S-ITS2 and Fe-hydrogenase regions of T. gallinae was performed to detect genetic heterogeneity, that could indicate the presence of other, possibly less virulent, strains. In 60/63 samples there was full alignment of sequences with the clonal strain of T. gallinae subtype A1. The remaining three samples had the same single synonymous nucleotide difference in the Fe-hydrogenase region; however, pathology is these three was alike to the others. Collectively, the results provide no clear evidence for less severe disease as explanation for the discrepancy in census data trends. We conclude that trichomonosis is a threat concealed in Dutch breeding greenfinch census data.